E-shop – the Innovative Way of Sale and Communication - Zdenka Šrámekova; Lucia Vilhanová (Polityki Europejskie, Finanse i Marketing)
Currently, e-shop is very common form of retail sale. Today's consumer is very demanding and increasingly prefers shopping from the comfort of his home. Therefore, individual businesses are trying to meet this trend and in addition to traditional forms of marketing they are also offering online purchasing options. However, e-shop offers a personal approach to dealing with customers and allows building long-term relationship.